Community Engagement Framework for A Sustainable Sea Turtle Conservation Marketing: A Conceptual Framework - Azizul Yadi Yaakop; Awangku Hassanal Bahar Pengiran Bagul; Fathilah Ismail (Penerbit UMS, 2021)
The engagement of local community in environmental and marine life conservation is crucial for the development of a successful conservation promotion and other related initiatives. This would possibly lead to a sustainable conservation and marine-based tourism and community based strategies for environmental planning and management. Given the attention of sea turtle conservation in the islands on the east coast of Peninsula Malaysia, the symbiotic relationship between local communities and the environment could become the most effective common marketing strategy in promoting sea turtle conservation, which has not been explored extensively now. Considering the above, this paper aims at developing a community engagement framework for a sustainable sea turtle conservation and other related tourism activities. The methodology of this conceptual paper is based on the development of community engagement factor as it was developed in previous studies. Besides that, the conceptual framework was also based on community perceptions over current scenario of sea turtle egg trade and local tourism authority matters. Apart from developing a novel community engagement framework for sea turtle conservation, the study will also raise the issue of understanding of marine life conservation from the eyes of the local community at the targeted settings. Since sea turtle conservation has a huge potential for Malaysia's marine-based tourism to explore and for the local communities to benefit from, it is hoped that the findings of this study will guide local government, Ministry of Tourism and Culture Malaysia and related NGOs to understand the role of community in sea turtle conservation related issues.